Accounting models and devolution in the Italian public sector (Pecvnia : Revista de la Facultad de Ciencias Económicas y Empresariales, Universidad de León, 2006)
In the 1990s Italy started a public sector administrative reform process consistent, in general terms, with the New Public Management movement. In particular, changes have been introduced in the budgeting and accounting systems of the State, municipalities, health care bodies, etc. In the same years an institutional reform also started and a strong power devolution process began to be realised; a shift to a federal form of the State seems to be the goal. Stating form the challenges coming from the devolution process, the article questions 1) if it is possible to find some shared features in theh reformed accounting systems of the different public sector organisation categories, and to shape in this way on or more accounting Italian models, and 2) if these models have an information capacity adequate to sustain the information needs- in terms of accountability, government co-ordination and decision making- emerging from the devolution process. The information needs in a devolved environment are recognised; eleven budgeting and accounting systems are analysed and compared. The issue of the consistency level existing between accountign and institutional reforms is also discussed.En la Italia de los años 90, se inició un proceso de reforma administrativa del sector público en consonancia, en términos generales, con el movimineto New Public Management. En concreto, se han introducido modificaciones en los sistemas contables y presupuestarios del Estado, de las corporaciones locales y de las instituciones sanitarias. Durante el mismo periodo se empreendió una reforma de carácter constitucional cuyo objetivo último parecía ser la constitución de un estado federal. A partir de los desafíos que supone todo proceso de descentralización, el artículo abre dos interrogantes: 1) la posibilidad de encontrar rasgos comunes en los sitemas contables reformados de los distintos niveles organizativos del sector público, con el fin de confirmar uno o varios modelos contables italianos y, 2) apreciar si estos modelos tienen la capacidad adecuada de una información que satisfaga las necesidades informativas en lo que se refiere a credibilidad, coordinación gubernamental y toma de decisiones que resulten de ese proceso de descentralización. Se identifican las necesiddes de información que se suscitan en la descentralización y se analizan y comparan once sistemas presupuestarios y contables. Igualmente, se discute el aspecto del grado de coherencia entre las reformas constitucionales y contables